Early Pliocene tracer of North Atlantic and South Pacific sea surface currents: Janthina typica (Bronn, 1860) (Mollusca: Gastropoda) - Meco, Joaquín; Lomoschitz, Alejandro; Betancort-Lozano, Juan Francisco (2017)
Janthina typica is an extinct, rare, floating species of gastropod from the early Pliocene whose fossils have an unusual geographic distribution, appearing in the eastern North Atlantic archipelagos (Canary, Azores, Madeira and Selvagen Islands), Morocco, and Pacific (New Zealand, Australia and Japan). This study examines the origin of this biogeography and how the species may have dispersed via sea surface currents. Janthina typica es un molusco gasterópodo flotante, extinguido y raro del Plioceno. Sus fósiles presentan una distribución geográfica inusual apareciendo en los archipiélagos del este del Atlántico norte (Islas Canarias, Azores, Madeira y Salvajes), en Marruecos y en el oeste del Pacífico (Nueva Zelanda, Australia y Japón). En el presente trabajo se estudia la causa de esta biogeografía y de su dispersión mediante corrientes marinas de superficie. 197 192 0,391 0,815 Q3 Q4 SCIE